Required separation distance between decks and at abutments of a bridge crossing a canyon site to avoid seismic pounding. - Bi, Kaiming (Earthquake engineering & structural dynamics.)
Major earthquakes in the past indicated that pounding between bridge decks may result in significant structural damage or even girder unseating. With conventional expansion joints, it is impossible to completely avoid seismic pounding between bridge decks, because the gap size at expansion joints is usually not big enough in order to ensure smooth traffic flow. With a new development of modular expansion joint (MEJ), which allows a large joint movement and at the same time without impeding the smoothness of traffic flow, completely precluding pounding between adjacent bridge decks becomes possible. This paper investigates the minimum total gap that a MEJ must have to avoid pounding at the abutments and between bridge decks. The considered spatial ground excitations are modelled by a filtered Tajimi-Kanai power spectral density function and an empirical coherency loss function. Site amplification effect is included by a transfer function derived from the one-dimensional wave propagation theory. Stochastic response equations of the adjacent bridge decks are formulated. The effects of ground motion spatial variations, dynamic characteristics of the bridge and the depth and stiffness of local soil on the required separation distance are analysed. Soil structure interaction effect is not included in this study. The bridge response behavior is assumed to be linear elastic.